El El libro de mis primos by Cristina Peri Rossi. The creation of a new order - Pasetti, Pía (2021)
El libro de mis primos (1969), novel by Cristina Peri Rossi (Montevideo, 1941), is built around a family governed by a hierarchical, authoritarian and violent system which towards the end is destroyed by “the cousins”, the children of the family. They are the ones who tear down the house of their ancestors, in a literal and symbolic sense. The fall of the family order is followed by the fall of a repressive state, so that both orders collapse simultaneously. In this way, at the same time, two oppressive and authoritarian institutions are demolished. In this article we are interested in exploring the intersections between both spheres, family and political, and for this, we will establish a dialogue with the Uruguayan political and social situation —which will be read within the Latin American revolutionary panorama—, at the time of publication of the novel. This is a moment of marked political agitation and effervescence, motivated, above all, by the triumphof the Cuban Revolution, the emergence of local and global social movements —particularly condensed in 1968—, and the near threat of the military dictatorships carried out in the Southern Cone, throughout the seventies.